Using Melon and Watermelon Peels for the Removal of Some Heavy Metals from Aqueous Solutions - Abdelrazeg Abdelrazeg; Aliaa Khalifa; Hana Mohammed; Hanan Miftah; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
In this study, the activated carbon of melon and watermelon peels was used as a solid adsorbent for the removal of ferric and copper ions from aqueous solutions through the batch equilibrium technique. The influence of contact time and initial concentration of metal ions on the adsorbed amount of metal ions was investigated. The highest adsorption capacity was found to be 3.32 and 74 mg of metal ions per gram of adsorbent at an initial concentration of 3.35 mg/L and 100 mg/L of ferric and copper ions, respectively. The melon peels were used and found to be 3.26 mg of metal ions per gram of adsorbent at an initial concentration of 3.35 mg/L, when watermelon was used, and this would be higher with a higher initial concentration. Ferric ion was removed by 86.83 - 99.55%, and copper ion by 18-88% along the whole range of initial concentrations when melon was used, and 77.55%-98.86% for ferric when watermelon was used. Isotherm studies showed that the data best fit the Langmuir isotherm model.